A new genus, Protaustrosimulium, for four species of Australian black flies (Diptera: Simuliidae) - Currie, Douglas C.; Craig, Douglas A.; Moulton, John K. (Zootaxa, 2018)
Protaustrosimulium n. gen. is described for four species: two previously named species from southeastern Australia—Paracnephia pilfreyi (Davies & Györkös 1988) and Paracnephia terebrans (Tonnoir 1925)—plus two newly described ones from the southwestern-most corner of Western Australia—Prot. amphorum n. sp. and Prot. opscurum n. sp. Molecular and morphological data suggest a close relationship between members of the new genus and Austrosimulium Tonnoir 1925. Monophyly of Protaustrosimulium is supported mainly by characters of adult females, as two of the four species are known only in that life stage. Two species groups are recognized: the pilfreyi-group for Prot. pilfreyi and Prot. amphorum, and the terebrans-group for Prot. terebrans and Prot. opscurum. The constituent species in each group are distributed vicariously in southeastern and southwestern Australia—a common biogeographical pattern in Australian simuliids.